2021
DOI: 10.1542/peds.2020-015404
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Management at Term and Late Preterm Birth: A Meta-analysis

Abstract: CONTEXT: The International Liaison Committee on Resuscitation prioritized scientific review of umbilical cord management at term and late preterm birth. OBJECTIVE: To assess effects of umbilical cord management strategies (clamping timing and cord milking) in infants ≥34 weeks’ gestational age. DATA SOURCES: Cochrane Central Register of Controlled Trials, Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
2
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 51 publications
(22 reference statements)
0
28
2
6
Order By: Relevance
“…Verzögertes Abnabeln wurde als Zeitraum ab 30 s nach der Geburt oder auch basierend auf physiologischen Parametern (z. B. nach einem Ende der Nabelschnurpulsationen oder nach dem Einsetzen einer Spontanatmung), exklusive eines Ausstreichens der Nabelschnur, definiert [ 92 , 93 ].…”
Section: Wissenschaftliche Grundlagen Auf Deren Basis Die Empfehlungen Für Die Praxis Zur Versorgung Und Reanimation Des Neugeborenen Berunclassified
See 2 more Smart Citations
“…Verzögertes Abnabeln wurde als Zeitraum ab 30 s nach der Geburt oder auch basierend auf physiologischen Parametern (z. B. nach einem Ende der Nabelschnurpulsationen oder nach dem Einsetzen einer Spontanatmung), exklusive eines Ausstreichens der Nabelschnur, definiert [ 92 , 93 ].…”
Section: Wissenschaftliche Grundlagen Auf Deren Basis Die Empfehlungen Für Die Praxis Zur Versorgung Und Reanimation Des Neugeborenen Berunclassified
“…Für Frühgeborene und späte Frühgeborene („late preterms“) aktualisierte eine ILCOR-Metaanalyse von 33 Studien (5236 Neugeborene), die eine verzögerte Abnabelung mit einer sofortigen Abnabelung für diese Patientengruppe verglich, die Ergebnisse einer früheren Cochrane-Studie aus dem Jahr 2013 [ 93 , 105 ]. Die Analyse zeigte keinen signifikanten Effekt auf die Mortalität (RR 2,54; 95 %-CI 0,50 bis 12,74; 4 Studien, 537 Neugeborene) oder die Notwendigkeit für Reanimationsmaßnahmen (RR 5,08; 95 %-CI 0,25 bis 103,58; 3 Studien, 329 Neugeborene).…”
Section: Wissenschaftliche Grundlagen Auf Deren Basis Die Empfehlungen Für Die Praxis Zur Versorgung Und Reanimation Des Neugeborenen Berunclassified
See 1 more Smart Citation
“…Unfortunately, none of the included trials reported on the primary outcome of survival without moderate to severe neurodevelopmental impairment in early childhood. By randomizing vigorous term infants to immediate cord clamping versus umbilical cord milking or to delayed versus immediate umbilical cord clamping, no significant differences in neonatal outcomes (including Apgar scores, need for resuscitation, or admissions to the neonatal intensive care unit) were found [21]. Recently, updated SpO 2 and HR percentiles in term infants with delayed cord clamping were published [22].…”
Section: Umbilical Cord Managementmentioning
confidence: 99%
“…Doğum sonrası göbek kordonunun klemplenme zamanı veya kordun sağılmasıyla ilgili çalışmalarda; geç kord klemplemenin Htc ve serum ferritin düzeylerini arttırdığı, mortaliyeti ve İVK riskini azalttığı, kan transfüzyonunda %10 azalma sağladığı, ancak kord sağmanın aşırı prematüre (<28 gebelik haftası) bebeklerde ciddi İVK riskini arttırdığı, hatta bazı çalışmalarda RDS riskini arttıryor gözüktüğü belirtilmekte olup, prematüre bebeklerde ideal kord uygulama yönteminin halen net olarak ne olduğununu bilinmediği, ancak erken kord klemplemenin (<30 sn) prematüre bebeklerde zararlı olabileceği nedeniyle bu bebeklere erken kord klemplemenin önerilmemesi gerektiği bildirilmektedir [6,[33][34][35][36][37][38][39][40]. Kord sağma işlemi prematüre bebeklerde serebrovasküler ve sistemik kan akımında fluktuasyonlara neden olabileceği için şu an önerilmemektedir [10].…”
Section: Non-farmakolojik öNlemlerunclassified